THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER SATISFACTION IN MSMES GEPREK KITHA BANDAR LAMPUNG - Bagas Jenisa Pratama; Vonny Tiara Narundana (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to analyze the influence of variables such as product quality and service quality on customer satisfaction in gaprek kitha MSMEs. The population that is the focus of the study is all geprek kitha MSME customers using a sample of 100 respondents from geprek kitha MSME customers using the Purposive Sampling technique. The analysis method used is multiple linear regression. The findings of this study show that product quality and service quality have a significant partial effect on customer satisfaction in prek kitha MSMEs. Simultaneously, or together, the variables of product quality and service quality have a significant effect on customer satisfaction and provide variations between variables by 84.8%, while 15.2% are influenced by other variables that are not contained in the study.